Correcting image distortions from a nonlinear B1+$$ {\boldsymbol{B}}_{1}^{+} $$‐gradient field in frequency‐modulated Rabi‐encoded echoes. Issue 5 (14th December 2022) - Wang, Paul; Froelich, Taylor; Torres, Efraín; DelaBarre, Lance; Jenkins, Parker; Radder, Jerahmie; Mullen, Michael; Garwood, Michael
Abstract : Purpose: To correct image distortions that result from nonlinear spatial variation in the transmit RF field amplitude ( B 1 + $$ B_1^{+} $$ ) when performing spatial encoding with the method called frequency‐modulated Rabi encoded echoes (FREE). Theory and Methods: An algorithm developed to correct image distortion resulting from the use of nonlinear static field ( B 0 ) gradients in standard MRI is adapted herein to correct image distortion arising from a nonlinear B 1 + $$ B_1^{+} $$ ‐gradient field in FREE. From a B 1 + $$ B_1^{+} $$ ‐map, the algorithm performs linear interpolation and intensity scaling to correct the image. The quality of the distortion correction is evaluated in 1.5T images of a grid phantom and human occipital lobe. Results: An expanded theoretical description of FREE revealed the symmetry between this B 1 + $$ B_1^{+} $$ ‐gradient field spatial‐encoding and standard B 0 ‐gradient field spatial‐encoding. The adapted distortion‐correction algorithm substantially reduced image distortions arising in the spatial dimension that was encoded by the nonlinear B 1 + $$ B_1^{+} $$ gradient of a circular surface coil. Conclusion: Image processing based on straightforward linear interpolation and intensity scaling, as previously applied in conventional MRI, can effectively reduce distortions in FREE images acquired with nonlinear B 1 + $$ B_1^{+} $$ ‐gradient fields.